Carbon Tariffs: Effects in Settings with Technology Choice and Foreign Production Cost Advantage - Drake, David F. (Manufacturing and Service Operations Management, 2018)
Emissions regulation is a policy mechanism intended to address the threat of climate change. However, the stringency of emissions regulation varies across regions, raising concerns over carbon leakage—an outcome where stringent regulation in one region shifts production to regions with weaker regulation. It is believed that such leakage adversely increases global emissions. It is also believed that leakage can be eliminated by carbon tariffs, which are taxes imposed on imported goods so that they incur the same emissions cost that they would have if they had been produced in the regulated region. Results here contradict these beliefs. This paper demonstrates that carbon leakage can arise despite a carbon tariff but, when it does arise under a carbon tariff, it decreases emissions. Due in part to this clean leakage, results here indicate that a carbon tariff decreases global emissions. Domestic firm profits, on the other hand, can increase, decrease, or remain unchanged due to a carbon tariff, which suggests that carbon tariffs are not inherently protectionist as some argue. Rather, results here suggest that carbon tariffs improve the efficacy of emissions regulation, enabling it to reduce global emissions in many settings in which it would otherwise fail to do so.The online appendix is available at https://doi.org/10.1287/msom.2017.0674 .